PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DI SEKOLAH DASAR NEGERI SE KECAMATAN BOGOR SELATAN - Dian Safitri; Ersam Mahendrawan; Lili Nurlaili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of transformational leadership, work motivation, and organizational culture on teacher performance in Public Elementary Schools in South Bogor District, both partially and simultaneously. This study uses a quantitative approach with an associative descriptive method. The study population was all Public Elementary School teachers in South Bogor District. The research sample consisted of 112 teachers determined using probability sampling techniques. Data collection techniques were carried out through the distribution of questionnaires using a Likert scale that had met validity and reliability tests. Data analysis used multiple linear regression analysis preceded by analysis prerequisite tests, namely normality, homogeneity, and linearity tests. Hypothesis testing was carried out using a t-test to determine the partial effect, an F-test to determine the simultaneous effect, and a coefficient of determination to determine the contribution of the independent variables to the dependent variable. The results showed that transformational leadership, work motivation, and organizational culture partially and simultaneously had a positive and significant effect on teacher performance in Public Elementary Schools in South Bogor District. The R Square (R²) value of 0.660 indicates that 66.0% of the variation in teacher performance can be jointly explained by transformational leadership, work motivation, and organizational culture, while the remaining 34.0% is influenced by other factors outside the research model that were not examined.